What can you do to save your translation shifts from destruction by social media - Al Shyiab, Mohammad M.; Wan Sulong, Wan Muhammad; Abdul Jabar, Mohd Azidan; Mohd Kasim, Zalina (Human Resource Management Academic Research Society (www.hrmars.com), 2023)
Social media has fundamentally altered how people share information and communicate, which has increased the frequency of translation errors in online content. Although translation shifts, or departures from the original text, are frequent, they can result in mistakes and misunderstandings, especially in delicate circumstances like legal or medical papers. This study explores the ways in which social media is affecting translation shifts and offers advice on how translators can navigate this new environment to protect the integrity of their work. It also scrutinizes the negative effects of social media on translation shifts and suggests strategies that translators may employ to defend their work and lessen their consequences. The study will be primarily concerned with the Arabic and English languages, and it will employ a mixed-methods approach to data collection and analysis, along with a quantitative analysis of translation changes in social media posts and a qualitative analysis of interviews with language specialists, professional translators, and social media users. The information is taken from a sample of Arabic-to-English translations on websites like Twitter and Facebook. The findings show that translation alterations in social media posts have significantly increased as compared to traditional media sources. Shifts most frequently occur as additions, omissions, and mistranslations. The results show that social media users are more likely to rely on machine translation technologies and casual language, increasing the chance of mistakes and discrepancies. In light of the tremendous influence that social media has on translation trends, it is important for professional translators to take action to uphold high translation quality standards. On the basis of the findings, concrete suggestions are offered for translators and social media users in order to improve the precision and caliber of online translations and safeguard the integrity of translation processes in the social media era.